2018
DOI: 10.3390/nu10091130
|View full text |Cite
|
Sign up to set email alerts
|

A Natural Dietary Supplement with a Combination of Nutrients Prevents Neurodegeneration Induced by a High Fat Diet in Mice

Abstract: Obesity and metabolic disorders can be risk factors for the onset and development of neurodegenerative diseases. The aim of the present study was to investigate the protective effects of a natural dietary supplement (NDS), containing Curcuma longa, silymarin, guggul, chlorogenic acid and inulin, on dysmetabolism and neurodegeneration in the brains of high fat diet (HFD)-fed mice. Decrease in the expression of FACL-4, CerS-1, CerS-4, cholesterol concentration and increase in the insulin receptor expression and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 60 publications
6
35
0
Order By: Relevance
“…We found a neuroprotective action of pistachio consumption, which partly prevented HFD-induced neuronal apoptosis, as demonstrated by a reduced number of cells with fragmented DNA in the cortical areas. Indeed, as we previously reported, the brain dysfunctions in long term HFD fed mice are associated with peripheral and central insulin resistance [5] and dyslipidemia [7]. For this reason, we verified the hypothesis that regular pistachio intake could influence glucose or lipid metabolism.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We found a neuroprotective action of pistachio consumption, which partly prevented HFD-induced neuronal apoptosis, as demonstrated by a reduced number of cells with fragmented DNA in the cortical areas. Indeed, as we previously reported, the brain dysfunctions in long term HFD fed mice are associated with peripheral and central insulin resistance [5] and dyslipidemia [7]. For this reason, we verified the hypothesis that regular pistachio intake could influence glucose or lipid metabolism.…”
Section: Discussionsupporting
confidence: 88%
“…Natural remedies are currently drawing attention as protective agents in treating obesity-related dysfunctions [6,7]. Food with antioxidant, anti-hyperlipidemia, and anti-inflammatory properties could help to reduce the risk of metabolic dysfunctions [8].…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of polyphenols have been investigated in relation to brain health. This review summarizes the neuroprotective activities of curcuminoids, silymarin, and chlorogenic acids, for which we recently explored the beneficial properties in preventing obesity-related neurodegeneration [57]. We delve into the efficacy of these natural compounds to counteract neuronal dysfunctions underlying AD pathogenesis.…”
Section: Dietary Natural Compounds and Neuroprotectionmentioning
confidence: 99%
“…In addition, NDS was able to prevent neuronal apoptosis. In fact, a tunnel assay showed that in brain cortical sections of NDS-treated HFD mice, the number of neurons with fragmented DNA (index of an impairment of cell survival) was significantly reduced compared to HFD untreated animals [57]. The beneficial effects of NDS are probably due to the well-documented anti-oxidative actions of curcumin, although a synergistic action of all polyphenolic compounds contained in NDS has to also be considered.…”
Section: Curcuminoidsmentioning
confidence: 99%
See 1 more Smart Citation